Student Understanding of PAI Subjects in Improving the Results of Madrasa Science Competitions at MTs Al-Mu'min Tasikmalaya - Siti Nur Janah; Asep Ahmad Sya’ban; Entin Kurniatin; Aa Fachry Fathul Barri; Dede Aji Mardani (al-Afkar, Journal For Islamic Studies, 2024)
This study aims to determine the effect of PAI subject abilities on students participating in Madrasah Science Competition in 2023 at MTs.al-Mu'min and to find out how students can help students in working on madrasa scientific competency questions integrated with PAI subjects. This research is a qualitative descriptive research with research subjects namely Social Sciences, Natural Sciences, Mathematics and PAI teachers as well as students of the Madrasah Science Competition in 2023. The research population is 8 people, consisting of 3 KSM 2023 participants, 1 MAPEL IPA teacher, 1 teacher Mapel Social Sciences, 1 Mathematics Mapel Teacher and 2 Mapel Teachers of Islamic Religious Education. Data collection techniques in this study use semi-structured interview techniques. The results showed that the ability of students' understanding in PAI subjects and PAI teacher assistance was very influential on the results of integrated madrasah science competencies.